Manajemen Pembelajaran Pelatihan Persiapan Program Magang - Fadilah, Arif Aji; Fakhruddin, Fakhruddin (Journal of Nonformal Education and Community Empowerment, 2019)
The purpose of this study is to describe the learning management in training preparation for Japan internship program at LPK Wakashio Gakkou, which includes planning, implementation, coaching, and evaluation of learning. The method used in this research is a qualitative approach. Data collection techniques used were interviews, observation, and documentation. The data validity technique uses triangulation of sources, methods and theories. Data analysis techniques include by data collection, data reduction, data presentation, and taking conclusions. The results of this study, know that learning planning is prepared by tutors based on user requests. Learning implementation is carried out intensively by using the dormitory as a compulsory residence for students, coaching is conducted relating to aspects of student's attitude / discipline during training activities. Evaluation of the results learning is carried out periodically, students are satisfied with the training activities provided by LPK Wakashio Gakkou for gaining knowledge in Japanese, work skills, good physical and disciplinary that are useful as provisions for internships to Japan.